Vpliv računskega polmera obračanja goseničnega vozila na potrebno moč motorja pri obračanju - Stojković, Vjekoslav (Strojniški vestnik, 2002)
This paper analyzes the impact of a fixed kinematic turning radius on the engine power required in a turn and on the load of friction elements in the turning mechanism of a tracked vehicle equipped with turning mechanisms that have several fixed kinematic turning radii. Parameters describing the relative change of engine power in a turn the relative change of braking power on the friction elements of the turning mechanism, and the change of efficiency coefficient of the turning mechanism depending on the relative turning radius are defined. Recommendations regarding the choice of fixed kinematic turning radii, relating to the design of the turning mechanism of a tracked vehicle, are given.
Keywords: goseničarji; obračanje vozil; moč motorjev; mehanizmi obračanja; vojaška vozila; obračanje; moč motorja